Physiological Changes at Altitude in Nonasthmatic and Asthmatic Subjects - Dianna Louie; Peter D Paré (Canadian Respiratory Journal, 2004)
Exercised-induced asthma is not due to exercise itself per se, but rather is due to cooling and/or drying of the airway because of the increased ventilation that accompanies exercise. Travel to high altitudes is accompanied by increased ventilation of cool, often dry, air, irrespective of the level of exertion, and by itself, this could represent an 'exercise' challenge for asthmatic subjects. Exercise-induced bronchoconstriction was measured at sea level and at various altitudes during a two-week trek through the Himalayas in a group of nonasthmatic and asthmatic subjects. The results of this study showed that in mild asthmatics, there was a significant reduction in peak expiratory flow at very high altitudes. Contrary to the authors' hypothesis, there was not a significant additional decrease in peak expiratory flow after exercise in the asthmatic subjects at high altitude. However, there was a significant fall in arterial oxygen saturation postexercise in the asthmatic subjects, a change that was not seen in the nonasthmatic subjects. These data suggest that asthmatic subjects develop bronchoconstriction when they go to very high altitudes, possibly via the same mechanism that causes exercise-induced asthma.